2018
DOI: 10.1097/mpg.0000000000001773
|View full text |Cite
|
Sign up to set email alerts
|

Celiac Disease Diagnosis Without Biopsy

Abstract: Sensitivity, specificity, positive, and negative predictive value of QUANTA Flash h-tTG IgA were excellent. The cut-off providing an optimized PPV for histological lesions compatible for celiac disease (Marsh ≥2) for the QUANTA Flash h-tTG IgA is 350 CU (15×) in adult and 560 CU (28×) in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 27 publications
1
3
0
1
Order By: Relevance
“…Longer time and lower rate of atTG normalization in CLIA group seem to support the previously published hypothesis of a higher sensitivity and dynamic range of this assay, which could distinguish between positive and negative results (9). This concept has an important clinical implication, since the commercial availability of 2 different tests could bring some confusion in atTG monitoring.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Longer time and lower rate of atTG normalization in CLIA group seem to support the previously published hypothesis of a higher sensitivity and dynamic range of this assay, which could distinguish between positive and negative results (9). This concept has an important clinical implication, since the commercial availability of 2 different tests could bring some confusion in atTG monitoring.…”
Section: Discussionsupporting
confidence: 83%
“…According to the literature (13), a cut off of 2.5 U/mL was used to discriminate between positive and negative samples. From June 2012, atTG IgA was performed using a CLIA method (QUANTA Flash h‐tTG IgA, San Diego, CA) on the platform BIOFLASH, using a cut‐off of 20 chemiluminescent units (9).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have evaluated whether this strategy can be applied in symptomatic adult CD. [10][11][12][13][14][15][16][17][18][19][20][21] These studies have suggested that tTG levels of ≥10×ULN could be predictive of CD in adults, and the recently published Finnish national guidelines for the diagnosis of CD have incorporated this diagnostic pathway into their practice. 22 However, this approach has not been widely adopted into adult clinical practice or guidelines.…”
Section: Coeliac Diseasementioning
confidence: 99%
“…Niños con TGA-IgA positivo, pero títulos más bajos (<10 veces el límite superior de lo normal), deben someterse a biopsias para disminuir el riesgo de diagnóstico falso positivo. [13][14][15] Las pruebas de HLA aún con presencia de síntomas no es criterio diagnóstico único, sin una serología positiva y diagnóstico basado en biopsia intestinal. 16,17 Hay personas que tienen más riesgo de desarrollar la enfermedad, sobre todo las que tienen familiares de primer grado afectos o las que padecen otras enfermedades en las que interviene el sistema inmune como la diabetes, enfermedad inflamatoria intestinal.…”
Section: -12unclassified